). Tell me what makes you laugh and I tell you what will happen: the role of humor daily events at work on the relationship between optimistic employees’, subjective well-being and adaptability at work - Junça Silva, A.; Caetano, António; Lopes, M. (IWP International Conference, 2014)
Introduction Research on positive affect in organizations supports that humor is an important factor at work, due to its positive effects on several outcomes, like creativity and well-being. However, there is a lack of research exploring specific humor daily events within work settings . Based on the affective events theory, we assume that humor at work can be classified as an affective event (i.e. produces an emotional reaction). As such, our aim is explore the mediating role of workers' humor daily events between optimism, well-being and adaptability at work. Objectives: Building on Affective Events Theory, we hypothesize: 1) that humor daily events will mediate the favorable effect of optimism on well-being, and; 2) humor daily events will mediate the relationship between optimism and adaptability. Method To test these hypothesis, employees from a call-center (N=51) filled in a diary questionnaire for ten consecutive working days after work. Results Both hypotheses were supported: 1) humor daily events mediated the relationship between optimism and subjective well-being, and 2) humor daily events mediated the relationship between optimism and adaptability. Further, adaptability and subjective well-being were positively correlated. Implications These findings suggest that the occurrence of humor related events during a working day might be a relevant uplift for the well-being of optimistic employees. Plus, one find that the higher number of humor daily events at work, the greater employees’ adaptability to their day-to-day challenges. These results suggest that training employees within optimistic strategies as well as promote conditions for the occurrence of humor daily events might play an important role on a working day. Further, employers and employees can feel better by enhancing the frequency of positive daily humor related events. Originality/Value The present study is one of the few studies to examine humor related events (for instance: tell a joke) within the working day, and the first to explore the mediating role of those situational factors on adaptability and subjective well-being.